Cost Volume Profit (CVP) Analysis As A Tool For Profit Planning In Cigarette Factory "Gudang Rasa" Kediri - Septiana, Sinta Nur; Aalin, Elmi Rakhma (Jurnal Ilmiah Cendekia Akuntansi; Vol 10 No 1 (2025): Januari, 2025)
The purpose of this research is to analyze Cost Volume Profit (CVP) as profit planning tool at Gudang Rasa Cigarette Factory, Kediri Regency in 2024. This research type was applied research with quantitative research method. Data collection techniques in this research were observation, literature study, and documentation. The data which was needed was data on production costs in 2021- 2023, sales data in 2021-2023, and data on expected profits in 2021-2023. The results of this research showed that Cost Volume Profit (CVP) analysis at Gudang Rasa Cigarette Factory, Kediri Regency, resulted in sales above the break-even point, which meant that the owner made profit and could cover all costs incurred. The calculation of Margin of Safety (MoS) resulted in sales being above the safe limit while the profit target expected by the owner had not been achieved yet. Gudang Rasa Cigarette Factory, Kediri Regency could implement Cost Volume Profit (CVP) analysis as profit planning tool for the coming year if the sales volume increased annually and the percentage of profit expected to be achieved exceeded Margin of Safety (MoS) .